PELAKSANAAN KOORDINASI CAMAT DALAM PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN KEPULAUAN MERANTI TAHUN 2019-2020 - ", Antika; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Riau Province, especially Meranti Islands Regency, is a coastal area that is rich in tropical forests and peat swamps. The area of peatland is 330,041 hectares, so it is one of the areas where forest and land fires are subscribed every year. In Meranti Islands Regency, there are sub-districts that have the highest hotspots in Rangsang sub-district as many as 222 and West Rangsang sub-district has the lowest hotspot with only 6 hotspots. Seeing the phenomenon that occurred, the Riau Provincial Government issued Regional Regulation Number 1 of 2019 concerning Technical Guidelines for Forest and Land Fire Management article 45 paragraph 3 regarding the Coordinator of the Camat in Controlling Land and/or Forest Fires.        The purpose of this study was to determine the implementation of sub-district coordination in controlling forest and land fires in Meranti Islands Regency in 2019-2020 and to determine the inhibiting factors for sub-district coordination in controlling forest and land fires in Meranti Islands Regency in 2019-2020. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques. The research locations were at the Rangsang Sub-district Office, Wonosari village, Citrapeace village, West Rangsang sub-district office, Bantar village, and Melai village.               The result of this research is that the coordination of the sub-district head in controlling forest and land fires in Rangsang and West Rangsang sub-districts has succeeded in minimizing the different understandings between the village government and the MPA group with the existence of collaborative programs carried out with the aim of controlling fires. There are 2 inhibiting factors for camat coordination: internal obstacles to miscommunication and external constraints, lack of public knowledge, and lack of infrastructure (equipment). Keywords: Coordination, Camat, Control